Evaluation of Cell Surface Vimentin Positive Circulating Tumor Cells as a Diagnostic Biomarker for Lung Cancer - Xie, Xiaohong; Wang, Liqiang; Wang, Xinni; Fan, Wan-Hung; Qin, Yinyin; Lin, Xinqing; Xie, Zhanhong; Liu, Ming; Ouyang, Ming; Li, Shiyue; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Background: Circulating tumor cells (CTCs) represent a collection of heterogeneous cells. Studies have shown epithelial CTCs and folate receptor (FR) positive CTCs could be used as diagnostic biomarkers for lung cancer (LC). This study aimed to determine whether cell surface vimentin (CSV) positive CTCs could be used as a biomarker for LC as well. Methods: 78 treatment-naïve non-small-cell lung cancer (NSCLC) patients, 21 patients with benign lung diseases (BLD) and 9 healthy donors (HD) were enrolled in this study. CTC detection was performed using CytoSorter® mesenchymal CTC kit (CSV). The correlation between CSV positive CTCs (CSV-CTCs) and LC patients’ clinicopathological characteristics would be evaluated, and diagnostic performances of CSV-CTCs and serum tumor markers for LC would be compared. Results: CTC detection rates (average CTC count: range) in LC patients, patients with BLD and HD were 83.33% (2.47: 0-8), 47.62% (0.5: 0-3) and 0% (0: 0), respectively. CSV-CTCs could be used to differentiate LC patients from the patients with BLD and HD (P < 0.0001). CSV-CTCs were correlated with cancer stage, lymph node involvement and distant metastasis (P = 0.0062, 0.0014 and 0.0021, respectively). With a CTC cut-off value of 2, CSV-CTCs would have a sensitivity and specificity of 0.67 and 0.87, respectively, for diagnosing LC. CSV-CTC positive rates showed statistical differences among HD, BLD patients and LC patients at different cancer stages (P < 0.0001). Furthermore, CSV-CTC positive rates were positively correlated with tumor size, lymph node involvement and distant metastasis (P = 0.0163, 0.0196 and 0.03, respectively). CSV-CTCs had a better diagnostic performance than serum tumor makers, such as carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cancer antigen 125 (CA125) and CA153. Conclusion: When CTC cut-off is set to 2 CTCs per 7.5 mL of blood, CSV-CTCs can be considered as an acceptable biomarker for diagnosing LC with a sensitivity and specificity of 0.67 and 0.87, respectively.